Pembentukan Akhlaq Melalui Pembiasaan Sebelum dan Sesudah Mengaji di Taman Pendidikan Al-Qur’an Nur-Ilmi Studi Kasus di Desa Karangpatihan Dusun Krajan Pulung Kab Ponorogo - Lintang Lutfhi Kirani; Ibnu Muchlis (Social Science Academic, 2025)
This study aims to find out how the formation of akhlaq trough habituation before and after reciting at TPA Nur-Ilmi, and also the values can be instilled in children at TPA Nur - Ilmi. The method used in this study is ABCD (Asset Based Community Driven – Development ) the method used form observing activities at nur – ilmi tpa and also working togheter to explore of potensial of children in tpa nur – ilmi. The result of observation show in tpa nur – ilmi has good habituasio for early childhood, and also inculcates morality by using religious values that have been applied in TPA Nur-Ilmi.